The influence of Cisplatin-based chemotherapy on the osseointegration of dental implants: An in vivo mechanical and histometrical study - Dantas, Marcos Vinícius Mendes [UNESP]; Verzola, Mário Henrique Arruda [UNESP]; Sanitá, Paula Volpato [UNESP]; Dovigo, Lívia Nordi [UNESP]; Cerri, Paulo Sérgio [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP] (Wiley, 2019)
Objectives: To evaluate the effect of Cisplatin on bone repair and mineralization around implants and on the mechanical properties of bone tissue. Materials and methods: Forty-three Wistar rats were randomly divided into two groups: Cisplatin (CIS, medication) and control (CTL, placebo solution), administered once a week for 4 weeks. After 4 weeks, implants were installed in both tibiae metaphysis. After 30 and 60 days, the animals were sacrificed and their femurs and tibiae were removed. Femurs were subjected to mechanical tests and tibiae for removal torque, arrangement and distribution of collagen fibers, morphometrical analyses (bone tissue in contact with the implant surface [BIC] and areal fraction between implant threads occupied by bone tissue [BAFO]) and scanning electron microscopy to calcium and calcium/phosphorus analysis. Data were analyzed by ANOVA or MANOVA, and Tukey or Games–Howell post hoc tests, respectively (α = 0.05). Results: The CTL specimens had significantly higher values (0.0001 ≤ p≤0.036) of strength (N), removal torque (N/cm2), %BIC, and %BAFO than CIS specimens, being their best results at day 60. No significant differences were found among the groups regarding the values of deformation, percentage of calcium, and calcium/phosphorus ratio. In CIS groups, there was a reduction in the organization of collagen at the bone/implant interface, resulting in a trabecular bone with thin trabeculae and birefringent collagen and irregular arrangement. Conclusions and clinical implications: Cisplatin interfered negatively in the repair and mineralization around dental implants, as well as on the quality of the bone tissue, mainly in the period of 30 days after the implant placement.
Keywords: Cisplatin; dental implantation; drug therapy; osseointegration